(untitled) (Ameghiniana, 2023)
The present study involves the palynological analysis of Late Ordovician–early Silurian samples coming from two wells drilled in the Llanos Basin of Colombia. Thirteen core samples of well A yielded a moderately preserved cryptospore assemblage comprising 17 taxa. Although composed mainly of simple forms without stratigraphic value, the marine organic-walled phytoplankton allows us to constrain the age of the palynological assemblage from the Late Ordovician (Katian–Hirnatian) to the early Silurian. A ditch-cutting sample of well B yielded marine organic-walled phytoplankton and one trilete spore species. The marine phytoplankton suggests an age no older than early Silurian for the assemblage of well B. The paleoenvironment of well A, interpreted as a braided fluvial channel system with sporadic and slight tidal influence, is supported by palynological data. The distribution of palynomorphs also suggests an increasing marine influence from the bottom to the top of the studied section. The cryptospore assemblage constitutes the first record of cryptospores of Colombia and northern South America and, therefore, the oldest evidence of land plants in this region. The presence of the trilete spore Ambitisporites avitus in strata of probably early Silurian age would represent the first record of Silurian sediments in the Llanos Basin and the oldest record of trilete spores in Colombia.